A multi-function glass shield for neutrons and gamma rays of boron- and bismuth-reinforced silicate glass - Hadeer M. Nasr El Din; Aly Saeed; Eman Salem; R. M. El Shazly; Magda Abdel Wahab (Scientific Reports)
Abstract A successful attempt to produce a multi-function glass shield for attenuating neutrons and gamma rays by reinforcing a silicate glass network with boron and bismuth has been accomplished. A composition of 20SiO2-80Na2O (BSiBi0) was proposed to be used as a host glass network and prepared using the melt/annealing techniques. The low concentration of SiO2 in BSiBi0 was not sufficient to form a stable glass network. Then, the proposed BSiBi0 was modified with 10, 20, 30, and 40 mol% of each of B2O3 and Bi2O3 (BSiBi1, BSiBi2, BSiBi3, and BSiBi4) simultaneously. The structural effects of adding B3+ and Bi3+ were studied through X-ray diffraction, density, and FTIR, which all showed enhancement of glass forming ability, a former role of Bi3+ ions, and crowded the glass network by BO4 units. The derived structural parameters $$-$$ - molar volume, mean silicon – silicon separation, mean boron – boron separation, oxygen packing density, packing density, and number of bridging/non-bridging oxygen $$-$$ - were extensively discussed to explore the impact of B3+ and Bi3+ on the formed network. The richness of the proposed host glass network by B3+ and Bi3+ enhanced its thermal stability. The obtained elastic properties by ultrasonic measurements reflect the increase of the glass rigidity with increasing concentrations of B3+ and Bi3+ ions. The obtained glasses have high visible light transparency and almost complete UV absorption. The measured shielding parameters against two types of neutron energies (total slow and slow) and a wide range of gamma rays’ energies showed a significant improvement in the shielding efficiency of the considered glasses. The total slow neutrons, slow neutrons, and gamma rays’ attenuation abilities were improved by 22.9, 135.5, and 73.8 $$-$$ - 199.5%. High thermal stability, elasticity, visible light transparency, and neutrons and gamma rays’ attenuation performance features give the produced glasses, especially BSiBi4 glass, preference as shielding materials in nuclear fields.